The role of place types on social relationships and satisfaction as influenced by COVID and disabilities - Brent Chamberlain; Valerie Novack; Teresa Larsen; Keunhyun Park; Keunhyun Park; Samuel Johnson; Jefferson Sheen; Motahareh Abrishami; Carlos Licon; Keith Christensen (Frontiers in Rehabilitation Sciences, 2025)
An individual's participation in community life is important to their health, well-being, self-determination, and quality of life. Consequently, community planners and policymakers play a role in shaping and improving environments through land use planning, including the distribution of amenities. This research explores the influence of different amenities, referred to as place types, and their influence on social satisfaction during and before the COVID-19 pandemic. A nationwide online survey of 393 adults across the U.S.A. was conducted to compare participants who self-report as living with and without a disability (41% and 59%, respectively). To uncover the relationship between place types and social satisfaction, participants responded to questions about social relationships, social satisfaction, frequency of visitation to place types, and the perceived importance of place types. Results indicate that the frequency of visits and perceived importance of place types were significantly associated with social satisfaction (r = 0.30, p = 0.001). Disability status, income level, population density, and employment status significantly predicted reduced visitation frequency during the pandemic (p < 0.001). Post-hoc comparisons revealed that individuals with disabilities experience a lower level of satisfaction with social life living closer to outdoor recreation (p = 0.006) and healthcare facilities (p = 0.025) compared to other place types. The findings emphasize the need for planners to better account for accessibility and inclusion in the design and combination of community amenities.